Premature Infants Have Normal Maturation of the T Cell Receptor Repertoire at Term - Morton, Sarah U.; Schnur, Maureen; Kerper, Rylee; Young, Vanessa; O’Connell, Amy E. (Frontiers in Immunology, 2022)
Premature infants are known to have immature immune systems compared to term infants; however, the impacts of ex utero immune development are not well characterized. Our previous retrospective clinical review showed prolonged T cell lymphopenia in a subset of extremely premature infants, suggesting that they may have lasting abnormalities in their T cell compartments. We used T cell receptor (TCR) repertoire sequencing to analyze the composition of the T cell compartment in premature and term infants in our NICU. We collected twenty-eight samples from individual subjects and analyzed the number of clonotypes, repertoire diversity, CDR3 length, and V gene usage between groups based on gestational age at birth and postmenstrual age at the time of sample collection. Further, we examined the TCR repertoire in infants with severe bronchopulmonary dysplasia (BPD) and those with abnormal T cell receptor excision circle (TREC) assays. Former extremely premature infants who were corrected to term postmenstrual age had TCR repertoire diversity that was more similar to term born infants than extremely premature infants, supporting normal maturation of the repertoire. Infants with severe BPD did not appear to have increased abnormalities in repertoire diversity. Decreased TCR repertoire diversity was associated with repeatedly abnormal TREC screening, although the diversity was within the normal range for subjects without low TRECs. This study suggests that extremely premature infants demonstrate normal maturation of the T cell repertoire ex utero. Further work is needed to better characterize postnatal T cell development and function in this population.